The symmetry in kinematics between the dominant and non-dominant legs in taekwondo turning kick [electronic resource] - 466690 Siau, Jun Xiong; Fakulti Pendidikan (2009)
Project Paper (Sarjana Muda Sains serta Pendidikan (Sains Sukan)) - Universiti Teknologi Malaysia, 2009